Indigenous Knowledge of Hydrologic Change in the Yukon River Basin: A Case Study of Ruby, Alaska - Wilson, Nicole J.; Walter, M. Todd; Waterhouse, Jon (ARCTIC, 2015)
In the Arctic and Subarctic, the contribution of Indigenous knowledge to understanding environmental change has been established over the last several decades. This paper explores the role of Indigenous knowledge of water in understanding hydrologic change within complex social-ecological systems. Observations of hydrology in the Yukon River Basin, contributed by 20 community experts from Ruby Village, Alaska, in semi-structured interviews, are compared with findings from scientific literature to illustrate the commonalities and differences. Research findings reveal the contribution of Indigenous knowledge to understandings of hydrologic change in the Yukon River and its tributaries, which includes insights regarding alterations in sediment and river ice regimes. Recommendations for future research that incorporates Indigenous knowledge of water to gain insight into hydrologic changes in the watershed include combining multiple case studies that are distributed geographically. Our findings suggest 1) that using participatory research approaches to research will help ensure that it benefits the communities whose livelihoods are affected by hydrologic changes, and 2) that a multidisciplinary approach that combines qualitative and quantitative methods from the social and biophysical sciences would be most effective to help us understand and respond to hydrologic changes. Dans l’Arctique et la région subarctique, l’apport des connaissances indigènes à l’égard de la compréhension de l’altération de l’environnement a été mis au clair au cours des dernières décennies. Cette communication explore le rôle des connaissances indigènes relativement à l’eau dans la compréhension des changements hydrologiques touchant les systèmes socioécologiques complexes. Les observations hydrologiques dans le bassin du fleuve Yukon, émanant de 20 experts communautaires de Ruby Village, en Alaska et prélevées dans le cadre d’entrevues semi-structurées, sont comparées aux constatations publiées dans des documents scientifiques pour ...